Incidence, compliance, and risk factor associated with central line-associated bloodstream infection (CLABSI) in intensive care unit (ICU) patients: S multicenter study in an upper middle-income country - Arulvani Rajandra; Nor’azim Mohd Yunos; Chin, Hai Teo; Anjanna Kukreja; Nur Alwani Suhaimi; Siti Zuhairah Mohd Razali; Sazali Basri; Shuan, Cindy Ju Teh; Chee, Loon Leong; Ismaliza Ismail; Azureen Azmel; Nor Hafizah Mohd Yunus; et al. (MDPI, 2025)
Despite significant prevention efforts, the incidence of central line-associated bloodstream infection (CLABSI) in intensive care units (ICUs) is rising at an alarming rate. CLABSI contributes to increased morbidity, mortality, prolonged hospital stays and elevated healthcare costs. This study aimed to determine the incidence rate of CLABSI, compliance with the central venous catheter (CVC) care bundle and risk factors associated with CLABSI among ICU patients. This prospective observational study was conducted in one university hospital and two public hospitals in Malaysia between October 2022 to January 2023. Adult ICU patients (aged > 18 years) with CVC and admitted to the ICU for more than 48 h were included in this study. Data collected included patient demographics, clinical diagnosis, CVC details, compliance with CVC care bundle and microbiological results. All data analyses were performed using SPSS version 23. A total of 862 patients with 997 CVCs met the inclusion criteria, contributing to 4330 central line (CL) days and 18 CLABSI cases. The overall incidence rate of CLABSI was 4.16 per 1000 CL days. The average of overall compliance with CVC care bundle components was 65%. The predominant causative microorganisms isolated from CLABSI episodes were Gram-negative bacteria (78.3%), followed by Gram-positive bacteria (17.4%) and Candida spp. (2.0%). Multivariate analysis identified prolonged ICU stay (adjusted odds ratio (AOR): 1.994; 95% confidence interval (CI): 1.092–3.009), undergoing surgery (AOR: 2.02, 95% CI: 1.468–5.830) and having had multiple catheters (AOR: 3.167, 95% CI: 1.519–9.313) as significant risk factors for CLABSI. Conclusions: The findings underscore the importance of robust surveillance, embedded infection-control and -prevention initiatives, and strict adherence to the CVC care bundle to prevent CLABSI in ICUs. Targeted interventions addressing identified risk factors are crucial to improve patient outcomes and reduce healthcare costs.